The Implementation of QDPR Method in Writing for EFL Learners Integrated Local Environmental Study - Arie Prasetyaningrum; Laila Wati; Yulia Kaswari; Usuludin Usuludin (Departement of Mathematics Education, 2024)
The goal of this study was to assess the effectiveness of teaching writing using the QDPR technique in grade X at MA Al-Majidiyah NWDI Majidi during the academic year 2023-2024. The study was pre-experimental in nature, with a single group pre-test and post-test. Twenty-three students participated. The data were collected from the students' pre- and post-tests, with the tests serving as the instrument. The data was analyzed using SPSS version 22 for Windows. The present researcher determined whether the data were normal using Shapiro Wilk before analyzing them using Paired Samples T-Test. The data were found to be normal and homogeneous using the Level Test for Homogeneity, which produced this result.The calculated Paired Sample T-test had a significance level of 0.00. The value was less than 0.05. This indicates that the alternative hypothesis was accepted, while the null hypothesis was rejected. Thus, during the academic year 2023-2024, that QDPR Method is helpful in teaching writing skill at MA Al-Majidiyah NWDI Majidi. Given the process and results of this study, the researcher advises that English teachers utilize this technique to teach writing.